The Effect of an Educational Intervention Based on the Health Action Process Approach on Nurses’ Communication Skills - Fattahi Ardakani, Mojtaba; Sotoudeh, Ahmad; Asadian, Ali; Heydari, Sara; Zareipour, Moradali (Investigación y Educación en Enfermería, 2024)
Objective. This study aimed to the effects of the Health Action Process Approach (HAPA) in promoting the quality of nurses' communication skills among nurses. Methods. The present quasi-experimental research was conducted on 148 nurses (76 in the intervention and 72 in the control group) in Yazd province (Iran). In this study, the total number of nurses in one hospital was selected as the intervention group, while the nurses from another hospital were chosen as the control group. The participants were recruited from public hospitals in Ardakan and Meibod cities. The data collection instrument was a questionnaire based on the Health Action Process Approach (HAPA) Constructs and a communicative skill questionnaire. The data were collected from the two groups before, one month after, and four months after the intervention. The control group did not receive any educational training during the course of the study. Results. In the pretest, no statistically significant difference was found between the intervention and control groups regarding the behavioral stages of effective communication with patients. In the posttest, the mean task self-efficacy score was significantly increased in the intervention group compared to the control (p<0.001). The mean coping self-efficacy score was also significantly higher in the intervention group than the control in the posttest (p<0.001). Moreover, the mean coping planning score was significantly increased in the post-test intervention group(p<0.001). The mean communicative skill score was also significantly increased in the intervention group compared to the post-test control (p=0.03). Conclusion. The intervention used in the present study based on the target model (HAPA) significantly affected nurses’ self-efficacy and communicative skills in the experimental group.